Improving Slope Stability of Lowwall Areas in Coal Mines: A Case Study - Kartini; Saptarini Dessy Lestari; Norfaeda Rahma; Khomaini Habib Sahal (E3S Web of Conferences)
Coal mining is an industry susceptible to slope failures, which can lead to significant economic losses and casualties. To mitigate this risk, a study was conducted to assess the stability of a post-landslide slope in the QR pit. The Factor of Safety (FOS) was calculated before and after slope improvement using Slide 6.0 software and the Bishop method. Results indicated that the initial FOS was 1.19, categorizing the slope as NOT STABLE. After improvement, the FOS increased to 1.33, classifying the slope as STABLE. The primary cause of the landslide was identified as groundwater activity, exacerbated by large cavities and cracks in the slope material. To address these issues, three potential mitigation measures were proposed: slope geometry modification, counterweight installation, and geomembrane application. The safety factor analysis necessitated the modification of the slope geometry to improve lowwall slope stability. This was achieved through the application of counterweights and geomembranes.